Draft Annual Plan Bihar 2011-12 Government of Bihar - Planning Commission (Planning Commission, 2011)
The size of the Annual Plan 2011-12 is Rs 24000.00 crore The outlay for the Annual Plan 2010-11 was Rs. 20000.00 crore. The outlay for the current plan is about 20.0 % more than that of the previous plan outlay.
Department of Planning & Development, Government of Bihar